Characterisation of Rhizobia on the Basis of Antibiotic Responses - R. Diwan, S. Sharma* and (Journal of Ecobiotechnology, 2011)
Rhizobium spp. were isolated from root nodules of 10 cultivated & three wild legume hosts. All the isolated Rhizobia were individually tested for their antibiotic response. Biodiscs of five antibiotics having three different concentrations viz: 0.5%, 1% & 1.5% were tested against the isolated Rhizobia using plate culture method. The affectivity of the antibiotics was revealed in terms of zone formation & was measured in mm.